Diurnal variation in brain injury after cardiac arrest and cardiopulmonary resuscitation - Peng, Fei; Wang, Fei; Gao, Bowen; Sun, Ping (Frontiers in Neurology, 2025)
BackgroundAlthough the circadian rhythm is known to influence several neurological diseases and response to treatments, its potential impact on brain injury following cardiac arrest and cardiopulmonary resuscitation (CA/CPR) remains unclear.MethodsWe performed a retrospective observational study on out-of-hospital cardiac arrest (OHCA) cases that presented to the emergency department of our hospital between September 2022 and August 2024. Based on the CA/CPR onset time, all patients were divided into two cohorts: daytime and nighttime groups. The gray-to white-matter signal intensity ratio (GWR) was analyzed using brain computed tomography (CT) images. We used the Cerebral Performance Category (CPC) to estimate the neurological outcomes. C-reactive protein (CRP), white blood cell (WBC) count, and monocyte (MONO) count levels in the plasma were also analyzed.ResultsOur study included 138 patients, of whom 68 were subjected to CA/CPR during daytime (8:00 to 20:00) and the remaining 70 were subjected to CA/CPR during nighttime (20:00 to 8:00). The imaging data showed that GWR values were significantly lower among patients subjected to CA/CPR during nighttime compared to those who were subjected to CA/CPR during daytime. Consistently, lower survival rates were observed among nighttime CA/CPR survivors. The CPC results indicated that a greater number of patients who underwent CA/CPR during daytime were rated as class 1–2 on day 3, day 5, and day 7 after achieving return of spontaneous circulation (ROSC). In contrast, a larger proportion of CA/CPR survivors in the nighttime group were rated as class 5 at the same time points. Elevated levels of C-reactive protein, white blood cell count, and monocyte count were observed in the plasma of survivors who underwent nighttime CA/CPR.ConclusionWe found that patients subjected to CA/CPR during nighttime (20:00–8:00) had worse neurological outcomes compared to those treated during daytime (8:00–20:00).